A Consumer Divided Cannot Stand. (June 2023) - Ghosh, Shubha
Should product disparagement give rise to an antitrust claim of monopolization or attempted monopolization? Majority of the courts have said no while some scholars are skeptical of these decisions. This article examines how conflicting visions of the consumer inform this debate. The conventional wisdom is that antitrust claims should adopt the principle of consumer welfare maximization with the assumption of the rational consumer, protected by product disparagement laws independent of antitrust. But if the consumer is not rational, the application of the consumer welfare standard needs to be re-examined. Specifically, product disparagement and antitrust claims are not independent or separable. This article examines the implications of the consumer division and examines both the consumer welfare assumption of conventional antitrust and its neo-Brandeisian critiques.